2021
DOI: 10.1177/00219983211047692
|View full text |Cite
|
Sign up to set email alerts
|

The wavenumber imaging of fiber waviness in hybrid glass–carbon fiber reinforced polymer composite plates

Abstract: Out-of-plane waviness is one of the most common defects which degenerates the strength, stiffness, and fatigue life of hybrid glass–carbon fiber–reinforced polymer composites (FRPs). An accurate and high-speed non-destructive testing method is highly desired for large composite structures in industries. Ultrasonic phased array is a great candidate for such application. This paper applies the wavenumber algorithm to image the waviness in hybrid FRP plates which are a multi-layered medium. The central frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…The attenuation loss of the ultrasound wave transmission in CFRP can be alleviated when the center frequency is approaching to the resonance frequency of the sample. That means the center frequency of the probe needs to satisfy the following conditions [41,42]: 16)…”
Section: Methodsmentioning
confidence: 99%
“…The attenuation loss of the ultrasound wave transmission in CFRP can be alleviated when the center frequency is approaching to the resonance frequency of the sample. That means the center frequency of the probe needs to satisfy the following conditions [41,42]: 16)…”
Section: Methodsmentioning
confidence: 99%
“…Schematic of a UT system setup with immersion detection is shown in Figure 4B. Depending on the transducer used, UT can be mainly classified as piezoelectric transducers (Cui et al, 2022), air-coupled transducers (ACT) (Liu et al, 2013, Liu et al, 2014, phased array ultrasonic transducers (PAUT) (Rizwan et al, 2021;Zhang et al, 2021), and electromagnetic acoustic transducers (EMAT) (Gao et al, 2010;Strass et al, 2017). However, EMAT transducers require a specific set-up to work on electrically non-conducting materials such as polymer composites.…”
Section: Ultrasonic Testingmentioning
confidence: 99%
“…The results indicated that both PAUT and SEUT can detect the hole with a minimum diameter of 0.8 mm and a thickness of 25 mm while signals of PAUT have better characteristics. Zhang et al (2021) proposed an efficient and accurate method to detect out-of-plane waviness in hybrid glass-carbon FRPCs plates using PAUT with 5MHz and 32 elements. Samples with different waviness angles were used for the experiments.…”
Section: Ultrasonic Testingmentioning
confidence: 99%
“…l 复合材料层合板由不同介质层叠加而成, 不同 介质层拥有不同的波速. 在复合材料层合板成像 中, 将超声相控阵收发的全矩阵数据 [15] 运用波外 推法将阵列虚拟的移动到第 层的顶部, 在每一层 实现超声波束聚焦, 多层介质被分为厚度为d l 的 不同均匀介质. 因此, 张海燕等 [16] 提出混合玻璃纤 维层的碳纤维增强复合材料层合板的正向模型为…”
Section: 全矩阵波数算法多层介质成像unclassified